Sexual violence victimisation and response among university students in sub-Saharan Africa: a scoping review protocol - Sylvia Kaaya; Rehema Chande Mallya; Marie Lindkvist; Ester Steven Mzilangwe; Faustine Kyungu Nkulu Kalengayi (BMJ Open)
Introduction Sexual violence (SV) is highly prevalent among university campuses across the globe, despite of several initiatives implemented to address it. Several studies have been published focusing on various aspects of SV on campuses. However, no review has been retrieved from the Joanna Briggs Institute (JBI) Database, Cochrane Library or Ovid examining evidence synthesis on prevalence, risk factors, victims and perpetrators, policies, laws and universities responses to SV in sub-Saharan Africa (SSA). This review aims to map the existing literature on SV victimisation among university students in SSA, related response strategies, and identify gaps in the evidence.Methods and analysis This review will follow JBI guidelines and will be conducted from 1 July 2023 to 31 December 2023. A team of five reviewers will screen eligible documents and articles for relevance from various data sources including electronic databases such as MEDLINE, EMBASE, PsycINFO, CINAHL, Google Scholar, PubMed and websites for government and agencies. Standard information for each study will be collected and a common analytical framework for all the primary documents will be conducted.Ethics and dissemination This review will involve analysis of published data only and therefore does not require ethics approval. The results will be published in a peer-reviewed journal.Registration This review has been registered with the Open Science Framework.